2000
DOI: 10.1074/jbc.m005179200
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Phosphorylation of DNA Topoisomerase II α by Protein Kinase CK2 Creates the MPM-2 Phosphoepitope on Ser-1469

Abstract: DNA topoisomerase II␣ is required for chromatin condensation during prophase. This process is temporally linked with the appearance of mitosis-specific phosphorylation sites on topoisomerase II␣ including one recognized by the MPM-2 monoclonal antibody. We now report that the ability of mitotic extracts to create the MPM-2 epitope on human topoisomerase II␣ is abolished by immunodepletion of protein kinase CK2. Furthermore, the MPM-2 phosphoepitope on topoisomerase II␣ can be generated by purified CK2. Phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 70 publications
(46 reference statements)
3
76
0
Order By: Relevance
“…In these yeast, topoisomerase II is hypo-phosphorylated and inactive, suggesting that it is a bona fide physiological target for CK2. Additionally, it was recently demonstrated in mammalian cells that CK2 phosphorylates residues on topoisomerase II␣, including Thr-1342, which are residues that are maximally phosphorylated in mitotic cells (32)(33)(34). In this study, we demonstrated that Pin1 inhibits the in vitro phosphorylation of Thr-1342 on topoisomerase II␣ by CK2 and that Pin1 interacts with topoisomerase II␣.…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…In these yeast, topoisomerase II is hypo-phosphorylated and inactive, suggesting that it is a bona fide physiological target for CK2. Additionally, it was recently demonstrated in mammalian cells that CK2 phosphorylates residues on topoisomerase II␣, including Thr-1342, which are residues that are maximally phosphorylated in mitotic cells (32)(33)(34). In this study, we demonstrated that Pin1 inhibits the in vitro phosphorylation of Thr-1342 on topoisomerase II␣ by CK2 and that Pin1 interacts with topoisomerase II␣.…”
mentioning
confidence: 57%
“…For example, CK2 was recently shown to phosphorylate residues on topoisomerase II␣ that are maximally phosphorylated in mitotic cells (33,34). These observations strongly suggest that topoisomerase II␣ is a mitotic target of CK2 in mammalian cells.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…In order to confirm the data obtained in vivo, we used three peptides in kinase assays (Figure 3c). One corresponded to the B domain of CDC25B, the second to a dodecapeptide (RRREDEESDDEE) classically used as CK2 substrate (Escargueil et al, 2000), and the third one to the middle part of the B domain of CDC25B, excluding the putative phosphorylation site (dotted line in Figure 3b). The ability of CK2 to phosphorylate these three peptides was evaluated by autoradiography after incubation with radiolabelled ATP in the presence of recombinant CK2 kinase.…”
Section: Identification Of Serines 186 and 187 Of Cdc25b As Targets Omentioning
confidence: 99%
“…In addition, CDK1 itself can be phosphorylated by CK2 (Russo et al, 1992) and CK2 has been implicated in the phosphorylation of cyclin B, which regulates its nuclear translocation (Li et al, 1997b). More recently, several proteins including the phosphatase PTP-S2 (Nambirajan et al, 2000), the SIX1 homeodomain (Ford et al, 2000) and the Topoisomerase II (Escargueil et al, 2000), were found to be phosphorylated by CK2 during mitosis. All these data suggest that CK2 plays a role in the control of the cell cycle and, particularly, at the G2/M transition.…”
Section: Introductionmentioning
confidence: 99%